Exploring Management Strategies for Freshwater Wetland: Policy Options for Southwest Coastal Region in Bangladesh - Kabir, Kazi Humayun; Aftab, Sharmin (Asian Development Policy Review, 2017)
Freshwater wetland plays a vital role in the national economy as well as the sustainable environment, natural habitats and the ecosystems in Bangladesh. Population explosion is still creating pressure on the limited resources like land, forest, water and specially the freshwater wetland. Over exploitation of resources, variety of economic, flood protection or control embankments, polders, dams, regulators, irrigation channels, dredging, settlements establishments like roads, bridges are the major threat to the freshwater wetland land in the southwest coastal Bangladesh. Thus, the sustainable management practices of existing wetlands need to be taken into considerations to conserve these resources. The wetland management strategies need to be directed at enriching wetland habitats with the component biological resources and also addressing the needs of the resident human population. Beel Dakatia of Dumuria Upazilla in Khulna District with 60 sq. mile is almost in the out of actions from agricultural productions, especially rice production due to water logging. However, the mercy of logged water has facilitated for fisheries, not properly or regularly managed. This study is conducted to seek the suitable or possible, acceptable by the different social groups, management policy options or guidelines that may foster sustainable management practices.